Negative Effects of Acid Violet-17 and MBB Dual In Vitro on Different Ocular Cell Lines. (3rd August 2017) - Hurst, José; Schnichels, Sven; Spitzer, Martin S.; Bartz-Schmidt, Karl-Ulrich; Farecki, Marie-Louise; Szurman, Peter; Januschowski, Kai
ABSTRACT: Purpose : Vital dyes have become a clinical standard during vitrectomy to visualize anatomical structures. It was the aim of this study to test the effect of two vital dyes (AV 17-M with 5% mannitol and MBB Dual) on different intraocular cells, to see whether in vitro test can be used as reliable preclinical testing tool. Methods : Cell morphology was assessed via phase contrast pictures, cell viability via MTS assay and total cell amount via crystal violet staining. ARPE19 and 661W cells were chosen for toxicology testing at different exposure times (60 seconds, 15 minutes and 30 minutes). Vital dyes were completely removed after the staining period. Results : Treatment with AV 17-M changed the morphology and the cell number at every time point investigated on ARPE19 and 661 W cells. ARPE19 cells treated with AV 17-M or MBB Dual displayed only a slight or no decrease in cell viability after the three different exposure times. AV-17 without medium to simulate a possible intraoperative use after fluid-air exchange showed a decrease in viability of 6%, 24% and 14%. A difference in cell density of 21%, 46% and 34% was noted after CV staining for AV 17-M, MBB Dual led to a decrease of 2%, 16% and 3% after 30 minutes compared to BSS. AV 17-M directly applied on 661W decreased viability significantly by 18% after 60 seconds, 33% after 15 minutes and 40% after 30 minutes. Cell density of 661W cells exposed relevant negative effects; after incubation of 60 seconds with AV 17-M, the cell amount was significantly lowered by 41% and MBB Dual by 12%. After 15 minutes, a loss of 48% cell amount was detected with AV 17-M and after 30 min 51%. MBB Dual led to 37% loss after 15 minutes and to 28% loss after 30 minutes. Conclusion : AV 17-M with 5% mannitol has a negative effect on different ocular cells.